Cycles of silence: First Nations women overcoming social and historical barriers in supportive cancer care. Issue 2 (16th January 2017) - Hammond, Chad; Thomas, Roanne; Gifford, Wendy; Poudrier, Jennifer; Hamilton, Ryan; Brooks, Carolyn; Morrison, Tricia; Scott, Tracy; Warner, Doris
Abstract: Background: First Nations people with cancer in Canada confront several critical inequities in physical and psychosocial domains. First Nations women are at a particular disadvantage as they are disproportionately affected by social determinants of health, but how they navigate these challenges within their communities is poorly understood. Objective: Our study explores survivorship experiences of First Nations women with cancer and their caregivers. Drawing from a larger data set on survivorship, we identify several major barriers to cancer communication and support in First Nations communities. Methods: Our team conducted a participatory, arts‐based study using several data collection methods (interviews, sharing sessions, photovoice, and other creative activities) with 43 participants (24 cancer survivors and 19 caregivers) from four First Nations communities in Canada. Results: Two major themes have emerged out of our data analyses: (1) suffering without support leads to cycles of silence and (2) community‐based supports can disrupt these cycles . We identified several social, historical, and institutional barriers to speaking about cancer and finding/providing support; however, communities met the challenge of silence through voluntary and unsolicited provision of support. Conclusions: Widespread silence around cancer reflects both the limited access First Nations people have to formal, supportive programs and services, as well as the creative ways they provide emotional, social, and financial support within their informal networks. Beyond the support of their communities, they also required institutional provision of care that is culturally safe, addressing the colonial impacts on cancer communication and the disproportionate burdens of disease in First Nations communities.